Possibilities of qPCR control of mycoplasma contamination of cell cultures - N. D. Yolshin; A. V. Petrov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Mycoplasmas are the main contaminants of cells cultures. They persist in cell cultures and can extensively affect host cell functions. Conducting experiments or producing protein in contaminated cultures are impractical. The aim of the study was to explore the possibility of quick detection of mycoplasma contamination of cell cultures and biotechnological products by a previously developed method which was modified to make it simpler and more affordable in Russia; and to assess the possibility of method validation for quality control. The authors chose the most applicable qPCR method of all qPCR methods currently used for mycoplasma detection, and modified it in the following way: expensive MGB-probes which cannot be synthesized in Russia were substituted by ordinary fluorescence probes. The reproducibility and sensitivity of the modified method were tested with M. hominis. The sensitivity of the test was equal to 10 mycoplasma gene copies per reaction. Comparison of the obtained results with regulatory requirements for mycoplasma detection showed that the proposed method complies with current official requirements and could be used as the main method for routine prompt cell culture testing for mycoplasma contamination.